Modelización teórica de la experiencia mimética y "Curso de acción" : análisis de situaciones de formación en enseñanza, salud y deporte - Serge Leblanc; Hélène Bouchot; Mélanie Secheppet (Universidade do Porto, 2020)
This paper presents a theoretical reflection to study the processes of work learning and development proceeding in the training environments which intentionally bring together the trainees to other people's world. These environments are built up from movies of real work or from observations in simulating and/or supported practices situations. These environments seek articulation between mimetic, reflexive, projective and ludic processes. Over the 2011-2020 period, three studies regarding video-training and/or simulation situations in various professional fields (teachers, midwifes and carriage drivers training) have been led within the framework of the empirical research program known as the "Course of action" or "enactive cultural anthropology". A theoretical modelling has been developed to account for these silent and complex social mimesis processes of linking agents experiences (immersion, imitation, emulation, "acting similarly to", representation, anticipation). This theoretical reduction based on the hexatomy of the course of action unit opens up some methodological paths to both better comprehend the implicit dimensions of body and sensitive activity, very active in this relation to other's world, and to better understand the performativity conditions of action (mimesis as a creative remake vs mimesis as a copy of reality).